Tensile strength of polyesteer with different composition of aluminium filler - Chong, Sia Onn (Universiti Malaysia Sarawak, UNIMAS, 2008)
Adhesive bonding is one of the most important joining methods available nowadays. So, it is important to know the properties of the adhesive in designing the product that required adhesive bond. Polyester resin, one of most widely used adhesive is tested in the project. The purpose of the project is to determine the strength of the polyester with different composition of aluminum filler in polyester resins. Three tests were conducted which are tested with different joint geometry, different overlap joint length and bulk specimen test. The results are interpreted in the diagram to make the comparison based on the strength, strain, and load to failure of test specimen. From the project, different methods has shows influence to the strength of polyester adhesive. The load to failure of polyester is varying from test to test because the load to failure is influenced by the changes in adhesive during testing. From the test, bulk specimen test for polyester resin shows lower strength than simple single lap joint test. Bulk specimen test show more precise reading than joint test. So, the data from bulk specimen test is more convenient to use as reference during designing